NILAI SOSIAL DALAM BIOGRAFI SANDIAGA UNO KERJA TUNTAS KERJA IKHLAS ONE WAY TICKET TO SUCCESS KARYA VALENTINA WIKAN - Sujoko Sujoko; Sindy Eka Putri (Universitas Batanghari, 2022)
This research aims to analyze the Social Value of Sandiaga Uno in the biography of Kerja Tuntas Kerja Ikhlas One Way Ticket To Success by Valentina Wikan. This research uses a qualitative approach with content analysis method. The data collection carried out by collecting quotations that are directly related to social values. Furthermore, the researcher classifies the data into the data classification table, then the next step is to analyze the data that has obtained in accordance with the theoretical foundation, which is to use a structural approach. The results showed that Sandiaga Uno's social value contained in Valentina Wikan's biography of Kerja Tuntas Kerja Ikhlas One Way Ticket To Success includes 3 social sub values: (1) 24 quotations of love values, (2) 28 quotations of social responsibility values, (3) 13 quotations of social values of harmony in life. Of the three social sub-values, there are 65 quotations found in the biography of Kerja Tuntas Kerja Ikhlas One Way Ticket To Success by Valentina Wikan. The results of this research concluded that the social sub-values contained in Kerja Tuntas Kerja Ikhlas One Way Ticket To Success by Valentina Wikan can be an example or reference in everyday life or to be applied in community life.